Genetic diversity and population structure of early-maturing tropical maize inbred lines using SNP markers - Adu, G.B.; Badu-Apraku, Baffour; Akromah, R.; García Oliveira, A.L.; Awuku, F.J.; Gedil, Melaku A (Public Library of Science, 2019)
Information on genetic diversity and population structure are very important in any breeding programme for the improvement of traits of interest and the development of outstanding products for commercialization. In the present study, we assessed the genetic diversity of 94 early-maturing white and yellow tropical maize inbred lines using single nucleotide polymorphism (SNP) markers. The larger number of SNP markers used in this study allowed a clearer inference of the population structure of the 94 inbred lines. Cluster analysis resolved the inbred lines into different clusters based on their pedigree, selection history and endosperm colour. However, three heterotic groups were revealed by population structure analysis, but additional field evaluation could be more informative to confirm the heterotic groups identified. Nevertheless, wide genetic variability existed among the inbred lines making them unique with the potential to contribute new beneficial alleles to maize breeding programmes in the tropics, especially in the West and Central Africa (WCA) sub-region.